TEKS BERJALAN DOTMATRIX DENGAN KEYBOARD BERBASIS ATMEGA32 - , MOCHAMAD IRVAN SEPTIANA; , Drs. Panggih Basuki, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Has been made a running dotmatrix text with keyboard based on ATMega32 used to present a variety of information such as information on the queue, warnings, etc. Made this tool will facilitate the presentation of information with dotmatrix display in the main attraction that entice people to read it. This tool system design using ATMega as the central processing system of data, dotmatrix driver, dotmatrix board, keyboard, and visual basic as the interface program. From the experiments have been conducted, dotmatrix been able to display a character through of data that is processed by the microcontroller and visual basic as the interface for the monitoring of the characters written on the keyboard with a serial cable connected to the microcontroller for display on PC.